Light Goose Conservation Order effects on nontarget waterfowl behavior and energy expenditure - Andrew J. Dinges; Elisabeth B. Webb; Mark P. Vrtiska (Wildlife Society Bulletin)
ABSTRACT When the Light Goose Conservation Order (LGCO) was established during 1999 in the Rainwater Basin of Nebraska, USA, LGCO activities were limited to 4 days/week and 16 public wetlands were closed to the LGCO to limit disturbance to nontarget waterfowl during this energetically important time period. However, the effects of LGCO activities on waterfowl behavior and energy expenditure are relatively unknown in this critical waterfowl staging area. To evaluate LGCO effects on target and nontarget species, we paired wetlands open and closed to LGCO and recorded waterfowl behavior and hunter encounters during springs 2011 and 2012. We constructed hourly energy expenditure models based on behavior data collected for mallards (Anas platyrhynchos) and northern pintails (A. acuta). In 2011, dabbling ducks (Anas spp.) spent more time feeding and less time resting in wetlands closed to hunting during early season when the majority of hunting encounters occurred; behaviors did not differ between hunt categories during late season when hunting activities subsided. However, in 2012, dabbling ducks spent more time feeding and less time resting in wetlands open to hunting during early and late seasons. We detected no differences in behaviors of lesser snow geese (Chen caerulescens) or greater white‐fronted geese (Anser albifrons) between hunting categories in early season. Mallards had slightly greater energy expenditure on wetlands closed to hunting (x¯ = 38.94 ± 0.31 kJ/bird/hr), compared with wetlands open to hunting (x¯ = 37.87 ± 0.32 kJ/bird/hr); therefore, greater energy spent by mallards cannot be attributed to hunting disturbance. We also detected no differences in dabbling duck behavior or energy expenditure between days open or closed to hunting in the region. A refuge system of wetlands closed to LGCO activities in the Rainwater Basin may be an important management strategy in providing reduced disturbance for nontarget waterfowl species in some years. Published 2016. This article is a U.S. Government work and is in the public domain in the USA.